When up brings you down: The effects of imagined vertical movements on motivation, performance, and consumer behavior. Issue 2 (11th December 2013) - Ostinelli, Massimiliano; Luna, David; Ringberg, Torsten
Abstract: Previous embodied cognition research suggests that "up" is associated with positivity (e.g., good, divine), whereas "down" is associated with negativity (e.g., bad, evil). We focus on the effect of vertical movements on consumer behavior and go beyond investigating mere affective associations of verticality. In five studies, we provide evidence that the mental simulation of vertical movements has counterintuitive effects on behavior—that is, imagining moving up hampers motivation and performance by boosting self‐worth. A pilot study shows that the imagination of vertical movements affects self‐worth. Studies 1, 2 and 3 show that imagining upward movements (e.g., taking an elevator ride up or taking off in an airplane) diminishes motivation as well as performance. Studies 4 and 5 show that imagining moving upward (downward) makes people feel better (worse) about themselves which, in turn, decreases (increases) their motivation to succeed on a subsequent task, hence worsening (improving) performance. This occurs independently of respondents' mood.